2015
DOI: 10.1097/dss.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Complications With New Oral Anticoagulants Dabigatran and Rivaroxaban in Cutaneous Surgery

Abstract: Because no patients on dabigatran or rivaroxaban experienced severe hemorrhagic complications during cutaneous surgery, a strategy of continuing these medically necessary medications during cutaneous surgery seems reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…The rationale for this is based on data from several peer-reviewed studies showing that the risk of hemorrhagic complications, dehiscence, or infection was not increased in patients taking anticoagulants compared with in controls. 1,4 Likewise, our findings did not show a significant difference in the rate of complications in patients taking NOACs compared with in all other patients who underwent MMS during the same period at this institution. The bleeding complication rate was 1.3% for patients receiving NOACs versus 0.7% for all other patients, and the infection rates were 2.6% and 1.1% respectively.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…The rationale for this is based on data from several peer-reviewed studies showing that the risk of hemorrhagic complications, dehiscence, or infection was not increased in patients taking anticoagulants compared with in controls. 1,4 Likewise, our findings did not show a significant difference in the rate of complications in patients taking NOACs compared with in all other patients who underwent MMS during the same period at this institution. The bleeding complication rate was 1.3% for patients receiving NOACs versus 0.7% for all other patients, and the infection rates were 2.6% and 1.1% respectively.…”
contrasting
confidence: 51%
“…To the Editor: Mohs micrographic surgery (MMS) has been reported to be safe, with a low incidence of adverse effects both intraoperatively and postoperatively. 1 Approximately 25% to 38% of patients who undergo cutaneous surgery are taking an antithrombotic agent that puts them at a slightly higher risk for bleeding. 2 Novel oral anticoagulants (NOACs) are an increasing presence in the dermatologist's office, as head-to-head clinical trials have shown them to have efficacy equal to superior that of warfarin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For warfarin, it is considered safe to operate if the INR is between 2 and 3.5 28 . Investigations of the novel oral anticoagulant agents (NOACs) including dabigatran, apixaban, and rivaroxaban have also demonstrated low hemorrhagic complication rates similar to those of traditional oral agents, and no severe or life‐threatening hemorrhagic complications 21,29,30 . At the current time, guidelines suggest continuing NOAC agents for dermatologic surgery 31,32 .…”
Section: Hemorrhagementioning
confidence: 99%
“…A retrospective review at a single center reported outcomes of 27 patients on dabigatran who underwent 41 cutaneous surgeries (Mohs micrographic surgery or basic excision) and 4 patients on rivaroxaban who underwent 5 cutaneous surgeries. 34 NOACs were continued in all patients. No hemorrhagic complications were observed in the rivaroxaban group, while one patient (3.7%) on dabigatran developed postoperative bleeding that was controlled with a pressure dressing.…”
Section: Dermatologic Proceduresmentioning
confidence: 99%